Association of subclinical hypothyroidism and HbA1c levels in non-diabetic subjects attending rural tertiary care centre in central India - Ram, Vidya Sagar; Kumar, Granth; Kumar, Manoj; Verma, Vivek Kumar; Kela, Dheeraj; Ali, Kasim (International Journal of Research in Medical Sciences, 2017)
Background: Subclinical hypothyroidism is defined as an elevated serum TSH level and normal concentrations of free T3 (FT3), free T4 (FT4), T3 and T4. A positive association between thyroid and diabetes mellitus is well recognized but to study the effect of thyroid disorders on glucose metabolism in non-diabetic patients is an area for extensive research. Present study was planned to assess correlation between subclinical hypothyroidism and glycosylated haemoglobin levels in non-diabetic patients. Methods: A case-control study was conducted on total 209 subjects. 109 patients were allotted in case group and 100 in control group. Controls were relatives and friends of patients who were matched for age and sex. Comparison between the case and the control groups were made using Student’s t-test (unpaired) and Box and Whisker Plot and regression graph were presented for correlation between serum TSH and HbA1c. Results: It was found that there was a positive correlation between the levels of serum TSH (µU/L) and HbA1c (%) in all the participants of the study by Pearson’s correlation coefficient (r=0.35, p < 0.0001). Conclusions: HbA1c levels are increased in subclinical hypothyroid patients. The effects of the elevated levels of Serum TSH on the HbA1c must be considered when interpreting the HbA1c for the diagnosis of diabetes or pre-diabetes in the subclinical hypothyroid patients.